Tobacco and alcohol during pregnancy: prevalence and determinants in Geneva in 2008 (Swiss Medical Weekly, 2013)
OBJECTIVES: To describe alcohol and tobacco consumption during pregnancy in women giving birth in a public hospital in Geneva, to evaluate risk factors related to these consumptions and to explore the influence of close relatives on the consumption habits of pregnant women. METHODS: A cross-sectional questionnaire survey after delivery in 207 women in the maternity ward of the Geneva University Hospitals in 2008. We used retrospective self-reports of smoking during pregnancy (including temporary smoking), smoking during the entire pregnancy and alcohol drinking during pregnancy (even a single glass). RESULTS: The proportion of smokers decreased from 31.2% before pregnancy to 21.7% during pregnancy (temporary smoking included), and 9.2% of women smoked continuously until delivery. Major factors associated with tobacco use were living alone, living with a smoker and tobacco consumption of the husband/partner in the presence of the pregnant woman. Regarding alcohol consumption, 62.7% of the participants reported drinking (even occasionally) before pregnancy, and 36.3% of the women drank at least one glass of alcohol during pregnancy. The alcohol consumption of the husband/partner and invitations to drink from other people were associated with alcohol consumption during pregnancy. CONCLUSIONS: Among women delivering in a public hospital, tobacco and alcohol consumption during pregnancy was important and significantly influenced by the habits and attitude of close relatives. The involvement of relatives in health promotion interventions should be addressed.